Protection Against Online Scams - Javeršek, Mirko (44th International Conference on Organizational Science Development: Human Being, Artificial Intelligence and Organization, Conference Proceedings, 2025)
Nature conservation and environmental protection are fundamental agendas in our postmodern world. The security of the environment can also be extended to the wider online environment. Thus, every moment we are exposed to new technological inventions and devices, as well as constantly new ways of using technology, at first glance more efficient. A more detailed look, however, with apparent greater productivity, shows that we are slowly drifting away and alienating ourselves from the essence. We are surrounded by technology, which sometimes we don't even know how to use properly. Various social networks, online forums and new applications are a source and a new environment for professional work and leisure. These new environments also carry significant security risks. The Internet represents a very useful and almost necessary tool for editing, sharing and accessing data for any purpose. So today, more than ever, we need to know its operation and the pitfalls that lie in wait for us. Coexistence with new ways of using technology is becoming more challenging. Let's look back to the bottom line and sharpen our perspective on the fact that we are in fact leading by example. In the eyes of male and female colleagues, male and female students, male and female students, we are not what we say, but what we live. Thus, in addition to nature conservation and environmental protection, we must also keep in mind the protection of the online environment.